Existence and Uniqueness of the Global Smooth Solution to the Periodic Boundary Value Problem of Fractional Nonlinear Schrödinger System (Journal of Partial Differential Equations, 2015)
" In this paper, we study a class of coupled fractional nonlinear Schr\u00f6dinger system with periodic boundary condition. Using Galerkin method, the existence of global smooth solution is obtained. We also prove the uniqueness of the solution."
Keywords: Nonlinear Schrödinger system; global smooth solution; Gagliardo-Nirenberg inequality